Relational and algebraic methods in computer science : 18th International Conference, RAMiCS 2020, Palaiseau, France, April 8-11, 2020, proceedings /: 18th International Conference, RAMiCS 2020, Palaiseau, France, April 8-11, 2020, proceedings. (©2020) - Unknown
No abstract available